2020
DOI: 10.1002/cbm.2178
|View full text |Cite
|
Sign up to set email alerts
|

Prisoners' understanding and experiences of parole

Abstract: Background: In Scotland, as elsewhere, there has been growing political and public interest in the function and process of parole accompanied by a lack of empirical research on the operation and effectiveness of parole. Aims: Against the backdrop of a Scottish Government review of parole aimed, among other things, at improving the transparency of the process, the aim of the study was to explore the experiences of prisoners seeking early release on licence. Methods: In conjunction with the Scottish Prison Servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
4
10
1
Order By: Relevance
“…Other women also talked about crying once they found out and being excited to go home to their families, especially their children. Unsurprisingly, the women's reports of positive feelings after being granted parole contrast with prior research focusing on the feelings of individuals denied parole who felt frustrated and upset (Kelly et al, 2020;West-Smith et al, 2000).…”
Section: Feelings Throughout the Processmentioning
confidence: 66%
See 4 more Smart Citations
“…Other women also talked about crying once they found out and being excited to go home to their families, especially their children. Unsurprisingly, the women's reports of positive feelings after being granted parole contrast with prior research focusing on the feelings of individuals denied parole who felt frustrated and upset (Kelly et al, 2020;West-Smith et al, 2000).…”
Section: Feelings Throughout the Processmentioning
confidence: 66%
“…The people they feel are going to come right back are released, and then they come back with new charges with longer stays." The common fear of denial is unsurprising, considering past research found that paroleseeking individuals feel anxiety before their hearing (Kelly et al, 2020).…”
Section: Feelings Throughout the Processmentioning
confidence: 99%
See 3 more Smart Citations